Clinical benefits of sex steroids given as a priming prior to GH provocative test or as a growth‐promoting therapy in peripubertal growth delays: Results of a retrospective study among ENDO‐ERN centres. (15th October 2020) - Galazzi, Elena; Improda, Nicola; Cerbone, Manuela; Soranna, Davide; Moro, Mirella; Fatti, Letizia Maria; Zambon, Antonella; Bonomi, Marco; Salerno, Mariacarolina; Dattani, Mehul; Persani, Luca
Abstract: Objectives: Sex steroids, administered as a priming before GH stimulation tests (GHST) to differentiate between growth hormone deficiency (GHD) and constitutional delay of growth and puberty (CDGP) or as growth‐promoting therapy using low‐dose sex steroids (LDSS) in CDGP, are much debated. We aimed to compare auxological outcomes of CDGP or GHD children undergoing primed or unprimed GHST and to evaluate LDSS treatment in CDGP. Design: Retrospective study among three paediatric University Hospitals in Italy and UK. Methods: 184 children (72 females) aged 12.4 ± 2.08 years underwent primed (/P + ) or unprimed (/P − ) GHST and were followed up until final height (FH). CDGP patients were untreated (CDG P − ) or received LDSS (CDGP + ). The cohort included 34 CDG P − /P +, 12 CDGP + /P +, 51 GHD/P +, 29 CDG P − /P −, 2 CDGP + /P − and 56 GHD/P − . FH standard deviation score (SDS), Δ SDS FH‐target height (TH) and degree of success (−1 ≤ Δ SDS FH‐SDS TH ≤ +1) were outcomes of interest. Results: GHD/P + had better FH‐SDS (−0.87 vs −1.49; P  = .023) and ΔSDS FH‐TH (−0.35 vs −0.77; P  = .002) than CDGP − /P + . Overall, GHD/P + showed the highest degree of success (90%, P  = .006). Regardless of priming, both rhGH and LDSS improved degree of success compared to no treatment (89% and 86% vs 63%, P  = .0009). GHD/P + showed a trend towards a higher proportion of permanent GHD compared to GHD/P ‐ (30.43% vs 15.09%; P  = .067). Conclusion: In peripubertal children, priming before GHST improves diagnostic accuracy of GHST for idiopathic GHD. LDSS treatment improves auxological outcomes in CDGP.